Phát triển chương trình giáo dục cho trẻ khuyết tật trí tuệ: Kinh nghiệm quốc tế và hàm ý cho Việt Nam - Lê Thị Tâm, Lê Thị Tâm; Nguyễn Thị Kim Hoa, Nguyễn Thị Kim Hoa; Lương Ngọc Hà, Lương Ngọc Hà; Nguyễn Thị Hà, Nguyễn Thị Hà; Mai Thị Phương, Mai Thị Phương (Tạp chí Giáo dục, 2026)
Curriculum developmentforstudents with intellectual disabilities has become an increasingly important area in the context of educational reform, aiming to ensure the right to learn and develop according to each student’s abilities and needs. The paper analyzes international experiences in developing educational programs for students with intellectual disabilities through five core components: objectives, content, teaching methods, assessment, and support policies. The findings reveal two main trends: 1) Adjusting elements of the general education curriculum to enhance inclusive learning opportunities, and 2) Developing special education or specialized skills programs to address the specific needs of this group of students. The study proposes that Vietnam should integrate both approaches in developing curricula for students with intellectual disabilities, ensuring alignment between policy and practice to improve educational quality and promote social inclusion for these learners.